Hospital‐acquired pressure injuries: The significance of the advanced practice registered nurse's role in a community hospital. Issue 4 (8th February 2017) - Irvin, Candice; Sedlak, Elizabeth; Walton, Christine; Collier, Susan; Bernhofer, Esther I.
Abstract: Background and purpose: Hospital‐acquired pressure injuries (HAPIs) continue to be a persistent problem in the acute care arena. The purpose of this retrospective quality improvement study was to examine if the introduction of nurse practitioners (NPs), as wound care consultants (WCCs), without other interventions, impacted the HAPI rates in a community hospital. Methods: A retrospective, comparison design was used; 48 months of HAPI data (May 2010–2014) reported on the monthly National Database for Nursing Quality Indicators (NDNQI) survey was abstracted from hospital records. Data included the assessment of 10, 752 patients and were divided into two groups for comparison: 24 months before and 24 months after NP hiring. Conclusions: There was a strong, inverse correlation between the presence of NPs and number of patients with HAPIs ( r = −0.73, p < .01), indicating that HAPI rates were significantly lower after NPs took on the role of WCCs. The odds of a HAPI occurring following introduction of the NP WCCs were 20% of the odds in the previous years. Implications for practice: Study findings suggest that NPs assuming a leadership role as WCCs may be instrumental in decreasing HAPI rates.